Ti3C2Tx MXene-Coated Electrospun PCL Conduits for Enhancing Neurite Regeneration and Angiogenesis - Nan, Li-Ping; Lin, Zeng; Wang, Feng; Jin, Xue-Han; Fang, Jia-Qi; Xu, Bo; Liu, Shu-Hao; Zhang, Fan; Wu, Zhong; Zhou, Zi-Fei; Chen, Feng; Cao, Wen-Tao; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Electrical signal is the key basis of normal physiological function of nerve, and the stimulation of electric signal also plays a very special role in the repair process of nerve injury. Electric stimulation has been shown to be effective in promoting axonal regeneration and myelination, thereby promoting nerve injury repair. At present, it is considered that electric conduction recovery is a key aspect of regeneration and repair of long nerve defects. Conductive neural scaffolds have attracted more and more attention due to their similar electrical properties and good biocompatibility with normal nerves. Herein, PCL and MXene-PCL nerve guidance conduits (NGCs) were prepared; its effect on nerve regeneration was evaluated in vitro and in vivo. The results showed the NGCs have good biocompatibility in vitro. Furthermore, a sciatic nerve defect model (15 mm) of SD rats was made, then the fabricated NGCs were implanted. MXene-PCL NGC showed similar results with the autograft in sciatic function index, electrophysiological examination, angiogenesis, and morphological nerve regeneration. It is possible that the conductive MXene-PCL NGC could transmit physiological neural electric signals, induce angiogenesis, and stimulate nerve regeneration. This paper presents a novel design of MXene-PCL NGC that could transmit self-originated electric stimulation. In the future, it can be combined with other features to promote nerve regeneration.